Air electrode / separator assembly and metal-air secondary battery
The air pole/separator junction with a hydroxide ion conductor and water-absorbing layer addresses zinc dendrite penetration and water loss issues, improving charging and discharging efficiency in metal air secondary batteries.
Patent Information
- Application Number
- JP2023510225
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2021-12-02
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2041-12-02
AI Technical Summary
Metal air secondary batteries face issues such as short circuits due to zinc dendrite penetration and decreased performance due to water evaporation and electrolyte loss, which affect charging and discharging efficiency.
An air pole/separator junction is designed with a hydroxide ion conductor like LDH separator, incorporating a water-absorbing layer and catalyst layers to manage water circulation and prevent dendrite penetration, enhancing charging and discharging performance.
The design ensures efficient water management and prevents short circuits, maintaining high performance and stability in metal air secondary batteries.
Smart Images

Figure 0007626839000001 
Figure 0007626839000002 
Figure 0007626839000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an air electrode / separator assembly and a metal-air secondary battery. [Background technology]
[0002] One of the candidates for innovative batteries is the metal-air secondary battery. Because oxygen, the positive electrode active material, is supplied from the air in metal-air secondary batteries, the space inside the battery container can be maximized for filling with the negative electrode active material, which in principle makes it possible to achieve a high energy density. For example, in zinc-air secondary batteries, which use zinc as the negative electrode active material, an alkaline aqueous solution of potassium hydroxide or the like is used as the electrolyte, and a separator (partition) is used to prevent short circuits between the positive and negative electrodes. During discharge, O2 is reduced on the air electrode (positive electrode) side to form OH, as shown in the following reaction formula: - is produced, while zinc is oxidized at the negative electrode to produce ZnO. Positive electrode: O2+2H2O+4e - →4OH - Negative electrode: 2Zn+4OH - →2ZnO+2H2O+4e -
[0003] Incidentally, it is known that in zinc secondary batteries such as zinc-air secondary batteries and nickel-zinc secondary batteries, metallic zinc precipitates in the form of dendrites from the negative electrode during charging, penetrates the voids of the separator such as nonwoven fabric, and reaches the positive electrode, resulting in a short circuit. Such a short circuit caused by zinc dendrites shortens the repeated charge / discharge life. In addition, in zinc-air secondary batteries, there is also a problem that carbon dioxide in the air passes through the air electrode and dissolves in the electrolyte, precipitating alkaline carbonates and reducing the battery performance. The same problem can also occur in lithium-air secondary batteries.
[0004] In order to address the above problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator that selectively allows hydroxide ions to pass through while preventing the penetration of zinc dendrites. For example, Patent Document 1 (WO 2013 / 073292) discloses that an LDH separator is provided between the air electrode and the negative electrode in a zinc-air secondary battery to prevent both short-circuiting between the positive and negative electrodes caused by zinc dendrites and the inclusion of carbon dioxide. In addition, Patent Document 2 (WO 2016 / 076047) discloses a separator structure that includes an LDH separator fitted or joined to a resin outer frame, and that the LDH separator has such high density that it is gas impermeable and / or water impermeable. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (WO 2016 / 067884) discloses various methods for forming an LDH dense membrane on the surface of a porous substrate to obtain a composite material (LDH separator). This method includes a step of uniformly attaching an origin substance capable of providing an origin of LDH crystal growth to a porous substrate, and subjecting the porous substrate to a hydrothermal treatment in a raw material aqueous solution to form an LDH dense membrane on the surface of the porous substrate. In addition, although it cannot be called LDH, LDH-like compounds are known as hydroxides and / or oxides having a layered crystal structure similar to LDH, and exhibit hydroxide ion conductive properties similar to LDH that can be collectively referred to as hydroxide ion conductive layered compounds. For example, Patent Document 4 (WO 2020 / 255856) discloses a hydroxide ion conductive separator comprising a porous substrate and a layered double hydroxide (LDH)-like compound that blocks the pores of the porous substrate.
[0005] In addition, in the field of metal-air secondary batteries such as zinc-air secondary batteries, an air electrode / separator assembly has been proposed in which an air electrode layer is provided on an LDH separator. Patent Document 5 (WO 2015 / 146671) discloses an air electrode / separator assembly having an air electrode layer including an air electrode catalyst, an electron conductive material, and a hydroxide ion conductive material on an LDH separator. Patent Document 6 (WO 2018 / 163353) discloses a method for producing an air electrode / separator assembly by directly bonding an air electrode layer including an LDH and carbon nanotubes (CNTs) on an LDH separator. Furthermore, Patent Document 7 (International Publication No. 2020 / 246176) discloses an air electrode / separator assembly comprising a hydroxide ion conductive separator, an interfacial layer covering one side of the separator and containing a hydroxide ion conductive material and a conductive material, and an air electrode layer provided on the interfacial layer and including an outermost catalyst layer composed of a porous collector and a layered double hydroxide (LDH) covering its surface. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 073292 [Patent Document 2] International Publication No. 2016 / 076047 [Patent Document 3] International Publication No. 2016 / 067884 [Patent Document 4] International Publication No. 2020 / 255856 [Patent Document 5] International Publication No. 2015 / 146671 [Patent Document 6] International Publication No. 2018 / 163353 [Patent Document 7] International Publication No. 2020 / 246176 Summary of the Invention
[0007] As mentioned above, metal-air secondary batteries using LDH separators have the excellent advantage of being able to prevent both short-circuiting between positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide. In addition, the denseness of the LDH separators also has the advantage of being able to suppress the evaporation of water contained in the electrolyte. However, since the LDH separators prevent the electrolyte from penetrating into the air electrode, no electrolyte is present in the air electrode layer. Therefore, compared to zinc-air secondary batteries using general separators (e.g., porous polymer separators) that allow the electrolyte to penetrate into the air electrode, circulation of water consumed or generated in the air electrode is impossible, leading to a decrease in charge / discharge performance. Therefore, a water absorption / discharge system that has the advantages of using an LDH separator while also exhibiting excellent charge / discharge performance is desired.
[0008] The present inventors have now found that a metal-air secondary battery exhibits excellent charge / discharge performance by providing a water absorbing / releasing layer below a discharge positive electrode and a charge positive electrode that sandwich a metal negative electrode enclosed in a hydroxide ion conductive separator such as an LDH separator in a battery case so as to be in contact with both the discharge positive electrode and the charge positive electrode. They have also found that an air electrode / separator assembly suitable for providing a metal-air secondary battery having such a water absorbing / releasing layer can be provided.
[0009] Therefore, an object of the present invention is to provide an air electrode / separator assembly which, while comprising a hydroxide ion conductive separator such as an LDH separator, exhibits excellent charge / discharge performance when used in a metal-air secondary battery.
[0010] According to the present invention, the following aspects are provided. [Section 1] a hydroxide ion conductive separator having an internal space capable of accommodating a metal negative electrode, or a metal negative electrode and an electrolyte-containing nonwoven fabric; a pair of catalyst layers covering both sides of the hydroxide ion conductive separator, the catalyst layers including an air electrode catalyst, a hydroxide ion conductive material, and an electrically conductive material; a pair of gas diffusion electrodes provided on the opposite sides of the pair of catalyst layers from the hydroxide ion conductive separator; a water absorbing / releasing layer having water absorbing and releasing properties and provided so as to be in contact with both of the pair of catalyst layers; An air electrode / separator assembly comprising: one of the pair of catalyst layers is a discharge catalyst layer, and the other of the pair of catalyst layers is a charge catalyst layer; a cathode / separator assembly in which the hydroxide ion conductive separator, the catalyst layer, and the gas diffusion electrode are arranged vertically, and the water absorbing / releasing layer is positioned below the catalyst layer. [Section 2] Item 2. The air electrode / separator assembly according to item 1, wherein the water absorbing / releasing layer contains a water absorbent resin. [Section 3] Item 3. The air electrode / separator assembly according to item 2, wherein the water absorbing / releasing layer further contains silica gel. [Section 4] Item 4. The air electrode / separator assembly according to item 2 or 3, wherein the water-absorbing resin is at least one selected from the group consisting of polyacrylamide-based resins, potassium polyacrylate, polyvinyl alcohol-based resins, and cellulose-based resins. [Section 5] 5. The air electrode / separator assembly according to any one of items 2 to 4, wherein the catalyst layer contains 0.01 to 10% by volume of the water-absorbing resin in terms of solid content, relative to 100% by volume of the solid content of the catalyst layer. [Section 6] Item 6. The air electrode / separator assembly according to any one of items 1 to 5, wherein the hydroxide ion conductive material contained in the catalyst layer is a layered double hydroxide (LDH). [Section 7] 7. The air electrode / separator assembly according to any one of items 1 to 6, wherein the catalyst layer contains 20 to 50% by volume of the hydroxide ion conductive material relative to 100% by volume of a solid content of the catalyst layer. [Section 8] Item 8. The air electrode / separator assembly according to any one of items 1 to 7, wherein the hydroxide ion-conductive separator is a layered double hydroxide (LDH) separator. [Section 9] Item 9. The air electrode / separator assembly according to item 8, wherein the LDH separator is composited with a porous substrate. [Section 10] The hydroxide ion conductive separator having the internal space may include a pair of hydroxide ion conductive separators facing each other or a folded hydroxide ion conductive separator, and the pair of hydroxide ion conductive separators or the folded hydroxide ion conductive separator may have their edges other than their upper ends (but excluding the folded edges) sealed by bonding (for example, heat sealing). , term 10. The air electrode / separator assembly according to any one of 1 to 9. [Section 11] The air electrode / separator assembly according to any one of items 1 to 10, a metal negative electrode accommodated in the internal space, and an electrolyte solution, water layer is located below the catalyst layer. [Section 12] Item 12. The metal-air secondary battery according to item 11, further comprising an electrolytic solution-containing nonwoven fabric in the internal space. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view conceptually showing an example of a metal-air secondary battery provided with an air electrode / separator assembly of the present invention. [Diagram 2] FIG. 2 is a diagram showing the layer configuration of the air electrode / separator assembly shown in FIG. 1 on the side including a discharge catalyst layer. [Diagram 3] FIG. 2 is a diagram showing the layer configuration of the side including the charging catalyst layer of the air electrode / separator assembly shown in FIG. 1. [Figure 4] FIG. 1 is a schematic cross-sectional view conceptually showing an LDH separator used in the present invention. [Figure 5A] FIG. 1 is a conceptual diagram showing an example of a He permeability measurement system used in Example A1. [Figure 5B] 5B is a schematic cross-sectional view of a sample holder and its surrounding structure used in the measurement system shown in FIG. 5A. [Figure 6] 1 is an SEM image of the surface of the LDH separator produced in Example A1. [Figure 7A]1 is a SEM image of the surface of carbon fibers constituting the carbon paper in the catalyst layer produced in Example B1. [Figure 7B] 7B is a magnified SEM image of the carbon fiber surface shown in FIG. 7A. [Figure 7C] 7B is an SEM image of a cross section near the surface of the carbon fiber shown in FIG. 7A. [Figure 8] FIG. 1 is an exploded perspective view of the evaluation cell produced in Example B1. [Figure 9] FIG. 1 is a schematic cross-sectional view of an evaluation cell produced in Example B1. [Figure 10] 1 is a graph showing charge-discharge cycle characteristics measured for the evaluation cells prepared in Examples B1 and B2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] FIG. 1 conceptually shows an example of a metal-air secondary battery including an air electrode / separator assembly of the present invention. The metal-air secondary battery 10 shown in FIG. 1 includes a negative electrode layer 22, a discharge positive electrode 14a (discharge air electrode layer), a charge positive electrode 14b (charge air electrode layer), and a water absorbing / releasing layer 20 in a battery case 30 including a substrate with a gas flow path having an air hole 30a. The negative electrode layer 22 includes an LDH separator 12 and a metal negative electrode 26 housed in the internal space of the LDH separator 12 (together with an electrolyte-containing nonwoven fabric 24). The metal negative electrode 26 includes a metal that serves as a negative electrode active material. The discharge positive electrode 14a is an air electrode layer used as a positive electrode during discharge. The charge positive electrode 14b is an air electrode layer used as a positive electrode during charge. The water absorbing / releasing layer 20 is provided so as to be in contact with the discharge positive electrode 14a and the charge positive electrode 14b. A water-repellent layer 28 is provided on the outside of the battery structure thus constructed, and the battery case 30 is fixed with screws at eight points on the end of the battery case 30. According to this configuration, the negative electrode layer 22 including the metal negative electrode 26 and the electrolyte-containing nonwoven fabric 24, which are enclosed in the LDH separator 12, the discharge positive electrode 14a disposed on one side of the metal negative electrode 26, and the charge positive electrode 14b disposed on the other side of the metal negative electrode 26 are arranged in a direction parallel to the LDH separator 12. 1 4b and a discharge positive electrode 1 4a and charging positive electrode 1A water absorbing and releasing layer 20 made of an acrylamide-based water-absorbent polymer material or the like and a space for installing the water absorbing and releasing layer 20 are provided so as to contact both of the upper and lower surfaces of the substrate 4b.
[0013] In FIG. 1, the air electrode / separator assembly 11 includes an LDH separator 12, a pair of air electrode layers 14 (a discharge positive electrode 14a and a charge positive electrode 14b) covering both sides of the LDH separator 12, and a water absorbing / releasing layer 20 (but does not include a metal negative electrode 26 and a nonwoven fabric 24). As shown in FIGS. 2 and 3, the air electrode / separator assembly 11 includes a discharge catalyst layer 16a and a gas diffusion electrode 18 laminated in order on one side of the LDH separator 12 to form a discharge positive electrode 14a, and a charge catalyst layer 16b and a gas diffusion electrode 18 laminated in order on the other side of the LDH separator 12 to form a charge positive electrode 14b. Therefore, by using the air electrode / separator assembly 11, a metal negative electrode 26, a nonwoven fabric 24 (if necessary), and an electrolyte, a metal-air secondary battery 10 can be easily constructed.
[0014] The metal-air secondary battery 10 illustrated in FIG. 1 is a three-electrode secondary battery in which a metal negative electrode 26, a discharge positive electrode 14a, and a charge positive electrode 14b, which are accommodated together with an electrolyte in the internal space of an LDH separator 12, are arranged in parallel to each other. This metal-air secondary battery 10 is preferably a stationary metal-air secondary battery. A stationary metal-air secondary battery is a stationary metal-air secondary battery that is installed after a predetermined space is secured, and is distinguished from a portable metal-air secondary battery. For convenience of explanation, the following explanation will be given assuming that the upper side in FIG. 1 is the upper side of the metal-air secondary battery 10. Below, each component of the metal-air secondary battery 10 will be explained in order.
[0015] LDH separator The metal-air secondary battery 10 shown in Fig. 1 is an embodiment in which a layered double hydroxide (LDH) separator is used as the hydroxide ion conductive separator. Note that, in the description of this specification, the contents related to the LDH separator are also applicable to hydroxide ion conductive separators other than the LDH separator, so long as technical consistency is not impaired. In other words, in the following description, the LDH separator can be read as the hydroxide ion conductive separator, so long as technical consistency is not impaired.
[0016] The LDH separator 12 is defined as a separator containing layered double hydroxide (LDH) and / or an LDH-like compound (hereinafter collectively referred to as hydroxide ion conductive layered compound), and selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive layered compound. In this specification, the term "LDH-like compound" refers to a hydroxide and / or oxide having a layered crystal structure similar to LDH, which may not be called LDH, and can be said to be equivalent to LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds. Such an LDH separator can be a known one as disclosed in Patent Documents 1 to 7, and an LDH separator composited with a porous substrate is preferred. A particularly preferred LDH separator 12 is one that contains a porous substrate 12a made of a polymer material and a hydroxide ion conductive layered compound 12b that plugs the pores P of the porous substrate, as conceptually shown in FIG. 4, and this embodiment of the LDH separator 12 will be described later. By including a porous substrate made of a polymer material, the battery can bend even when pressurized and is not easily broken, so that the battery can be housed in a battery container and pressurized in a direction in which the battery elements are in close contact with each other together with other battery elements (negative electrode, etc.). Such pressurization is also advantageous when a battery module is constructed by housing a plurality of stacked batteries in one module container. For example, by pressurizing a zinc-air secondary battery, the gap that allows the growth of zinc dendrites between the negative electrode and the LDH separator 12 can be minimized (preferably eliminated), which is expected to more effectively prevent the extension of zinc dendrites.
[0017] However, in the present invention, various hydroxide ion conductive separators can be used, not limited to the LDH separator 12. The hydroxide ion conductive separator is defined as a separator containing a hydroxide ion conductive material, which selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive material. Thus, the hydroxide ion conductive separator has gas impermeability and / or water impermeability, particularly gas impermeability. That is, the hydroxide ion conductive material constitutes all or a part of the hydroxide ion conductive separator with such high density that it exhibits gas impermeability and / or water impermeability. The definition of gas impermeability and / or water impermeability will be described later with respect to the LDH separator 12. The hydroxide ion conductive separator may be composited with a porous substrate.
[0018] Metal anode The metal negative electrode 26 contains an active material (negative electrode active material), and an oxidation reaction of the active material occurs during discharge, and a reduction reaction occurs during charge. Metals such as zinc, lithium, sodium, calcium, magnesium, aluminum, and iron are used as the negative electrode active material, and may contain oxides of these metals.
[0019] The negative electrode layer 22 has a configuration in which a metal negative electrode 26 is accommodated in the internal space of the LDH separator 12 together with a nonwoven fabric 24 for holding an electrolyte that covers the metal negative electrode 26, and an excess space can be provided above in consideration of the generation of gas such as H2 gas during the charge / discharge reaction. The metal negative electrode 26, the nonwoven fabric 24, and the like are inserted into the internal space of a pair of LDH separators 12 whose upper ends are opened to form a bag shape and whose three outer edges (other than the upper ends) are heat-sealed, and after the electrolyte is injected, the upper open end of the negative electrode layer 22 is sealed by heat sealing. In addition, the metal negative electrode 26 is accommodated in the internal space of the LDH separator 12 with the lead portion of the metal negative electrode 26 extending from the upper portion of the negative electrode layer 22.
[0020] Discharge positive electrode The discharge positive electrode 14a has a catalyst capable of reducing oxygen, and water, oxygen gas supplied from the atmosphere, and electrons react to produce hydroxide ions (OH - ) occurs. This discharge positive electrode 14a needs to be provided so that oxygen gas contained in the atmosphere can diffuse. For example, the discharge positive electrode 14a is configured so that at least the surface of the discharge positive electrode 14a is exposed to the atmosphere, and the current collector is desirably made of a material that is porous and has electronic conductivity.
[0021] The discharge positive electrode current collector is not particularly limited as long as it is made of a conductive material having gas diffusion properties, but is preferably made of at least one selected from the group consisting of carbon, nickel, stainless steel, and titanium, and more preferably carbon. Specific examples of the porous current collector include carbon paper, nickel foam, stainless steel nonwoven fabric, and any combination thereof, and is preferably carbon paper. Commercially available porous materials can be used as the current collector. The thickness of the porous current collector is preferably 0.1 to 1 mm, more preferably 0.1 to 0.5 mm, and even more preferably 0.1 to 0.3 mm, from the viewpoint of ensuring a wide reaction region, that is, a three-phase interface consisting of an ion-conducting phase (LDH), an electron-conducting phase (porous current collector), and a gas phase (air). The porosity of the discharge catalyst layer 16a is preferably 70% or more, more preferably 70 to 95%. In particular, in the case of carbon paper, it is more preferably 70 to 90%, and particularly preferably 75 to 85%. The above porosity ensures excellent gas diffusion and a wide reaction area. In addition, since there is a large amount of pore space, clogging with generated water is unlikely to occur. The porosity can be measured by mercury intrusion porosimetry.
[0022] The discharge positive electrode 14a preferably includes a conductive porous material having gas diffusion properties, a discharge catalyst, and a binder. This allows a three-phase interface in which oxygen gas, water, and electrons coexist to be formed on the catalyst, and allows the discharge reaction to proceed. The catalyst is preferably one having oxygen reduction ability, and examples of such catalysts include (i) nickel, (ii) platinum group elements such as palladium and platinum, (iii) perovskite oxides containing transition metals such as cobalt, manganese, and iron, (iv) noble metal oxides such as ruthenium and palladium, (v) manganese oxide, and (vi) any combination thereof. The catalyst is preferably fine particles in order to increase the reaction field. Specifically, the particle size of the catalyst is preferably 5 μm or less, more preferably 0.5 nm to 3 μm, and even more preferably 1 nm to 3 μm.
[0023] The hydroxide ion conductive material contained in the catalyst layer 16 has a spherical, plate-like, or strip-like shape, and forms a conductive path throughout the catalyst layer. The hydroxide ion conductive material is not particularly limited as long as it has hydroxide ion conductivity, but is preferably LDH. The composition of LDH is not particularly limited, but is preferably a compound having the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is at least one divalent cation, and M 3+ is at least one trivalent cation, and A n- is an anion with a valence of n, n is an integer of 1 or more, x is 0.1 to 0.4, and m is an arbitrary real number). 2+ can be any divalent cation, but preferred examples include Ni 2+ , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ Examples include: 3+ can be any trivalent cation, but preferred examples include Fe3+ , Al 3+ , Co 3+ ,Cr 3+ , In 3+ In particular, in order for LDH to have both catalytic activity and hydroxide ion conductivity, M 2+ and M 3+ Each of the transition metal ions is preferably a transition metal ion. 2+ Ni 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ and the like. Particularly preferred is Ni. 2+ On the other hand, the more preferred M 3+ Fe 3+ , Co 3+ ,Cr 3+ and the like, and particularly preferably Fe. 3+ In this case, M 2+ Part of the 2+ , Ca 2+ , Z 2+ may be substituted with a metal ion other than a transition metal, such as M 3+ Part of the material is Al. 3+ , In 3+ It may be substituted with a metal ion other than a transition metal such as A. n- can be any anion, but a preferred example is NO 3- , CO3 2- , SO4 2- , O.H. - , Cl - , I - , Br - , F - More preferably, NO3 - and / or CO3 2- Therefore, the above general formula is M 2+ Ni 2+ Including M 3+ Fe 3+ Including A n- NO3 - and / or CO3 2-It is preferable that the formula contains the formula: n is an integer of 1 or more, preferably 1 to 3. x is an integer of 0.1 to 0.4, preferably 0.2 to 0.35. m is an arbitrary real number. More specifically, m is a real number or integer of 0 or more, typically greater than 0 or 1 or more.
[0024] The content of the hydroxide ion conductive material contained in the catalyst layer 16 is preferably an amount that allows an ion conductive path to be formed within the catalyst layer 16. Specifically, the content is preferably 10 to 60 volume %, more preferably 20 to 50 volume %, and even more preferably 20 to 40 volume %, relative to 100 volume % of the solid content of the catalyst layer 16. On the other hand, the conductive material contained in the catalyst layer 16 is preferably at least one selected from the group consisting of conductive ceramics and carbon-based materials. Preferred examples of conductive ceramics include LaNiO3, LaSr3Fe3O 10 Examples of carbon-based materials include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, Ketjenblack, and any combination thereof.
[0025] A known binder resin can be used as the binder contained in the catalyst layer 16. Examples of organic polymers include butyral resins, vinyl alcohol resins, celluloses, vinyl acetal resins, polytetrafluoroethylene, polyvinylidene fluoride, etc., and butyral resins, polytetrafluoroethylene, and polyvinylidene fluoride are preferred.
[0026] Positive electrode for charging The charging positive electrode 14b has a catalyst capable of generating oxygen, and generates hydroxide ions (OH - ) generates oxygen, water, and electrons. In this charging positive electrode 14b, the charging reaction proceeds at a three-phase interface where oxygen gas, water, and an electron conductor coexist. For this reason, the charging positive electrode 14b is configured so that oxygen gas generated by the charging reaction can diffuse, and the current collector is desirably made of a porous and electron-conductive material.
[0027] The charge positive electrode collector is not particularly limited as long as it is made of a conductive material having gas diffusion properties, as in the discharge positive electrode collector, but is preferably made of at least one selected from the group consisting of carbon, nickel, stainless steel, and titanium, and more preferably carbon. Specific examples of the porous collector include carbon paper, nickel foam, stainless steel nonwoven fabric, and any combination thereof, and is preferably carbon paper. Commercially available porous materials can be used as the collector. The thickness of the porous collector is preferably 0.1 to 1 mm, more preferably 0.1 to 0.5 mm, and even more preferably 0.1 to 0.3 mm, from the viewpoint of ensuring a wide reaction region, that is, a three-phase interface consisting of an ion-conducting phase (LDH), an electron-conducting phase (porous collector), and a gas phase (air). The porosity of the charge catalyst layer 16b is preferably 70% or more, more preferably 70 to 95%. In particular, in the case of carbon paper, it is more preferably 70 to 90%, and particularly preferably 75 to 85%. The above porosity ensures excellent gas diffusion and a wide reaction area. In addition, since there is a large amount of pore space, clogging with generated water is unlikely to occur. The porosity can be measured by mercury intrusion porosimetry.
[0028] The hydroxide ion conductive material contained in the charging positive electrode 14b is not particularly limited as long as it is a material having hydroxide ion conductivity. and The composition of LDH is not particularly limited, but is preferably a compound represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is at least one divalent cation, and M 3+ is at least one trivalent cation, and A n- is an anion with a valence of n, n is an integer of 1 or more, x is 0.1 to 0.4, and m is an arbitrary real number).2+ can be any divalent cation, but preferred examples include Ni 2+ , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ Examples include: 3+ can be any trivalent cation, but preferred examples include Fe 3+ , Al 3+ , Co 3+ ,Cr 3+ , In 3+ In particular, in order for LDH to have both catalytic activity and hydroxide ion conductivity, M 2+ and M 3+ Each of the transition metal ions is preferably a transition metal ion. 2+ Ni 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ and the like. Particularly preferred is Ni. 2+ On the other hand, the more preferred M 3+ Fe 3+ , Co 3+ ,Cr 3+ and the like, and particularly preferably Fe. 3+ In this case, M 2+ Part of the 2+ , Ca 2+ , Zn 2+ may be substituted with a metal ion other than a transition metal, such as M 3+ Part of the material is Al. 3+ , In 3+ It may be substituted with a metal ion other than a transition metal such as A. n- can be any anion, but a preferred example is NO 3- , CO3 2- , SO4 2- , O.H. - , Cl - , I - , Br - , F - More preferably, NO3- and / or CO3 2- Therefore, the above general formula is M 2+ Ni 2+ Including M 3+ Fe 3+ Including A n- No 3- and / or CO3 2- It is preferable that the formula contains the formula: n is an integer of 1 or more, preferably 1 to 3. x is an integer of 0.1 to 0.4, preferably 0.2 to 0.35. m is an arbitrary real number. More specifically, m is a real number or integer of 0 or more, typically greater than 0 or 1 or more.
[0029] The air electrode catalyst contained in the charging positive electrode 14b is preferably at least one selected from the group consisting of LDH and other metal hydroxides, metal oxides, metal nanoparticles, and carbon-based materials, and more preferably at least one selected from the group consisting of LDH, metal oxides, metal nanoparticles, and carbon-based materials. The LDH is as described above for the hydroxide ion conductive material, and is particularly preferable in that it can function as both an air electrode catalyst and a hydroxide ion conductive material. Examples of metal hydroxides include Ni-Fe-OH, Ni-Co-OH, and any combination thereof, which may further contain a third metal element. Examples of metal oxides include Co3O4, LaNiO3, LaSr3Fe3O 10 Examples of the metal nanoparticles (typically metal particles having a particle size of 2 to 30 nm) include Pt and Ni-Fe alloys. As described above, examples of the carbon-based material include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof. From the viewpoint of improving the catalytic performance of the carbon-based material, it is preferable that the carbon-based material further contains a metal element and / or other elements such as nitrogen, boron, phosphorus, and sulfur.
[0030] The organic polymer contained in the charging positive electrode 14b may be a known binder resin. Examples of the organic polymer include butyral resin, vinyl alcohol resin, cellulose, vinyl acetal resin, etc., and preferably butyral resin.
[0031] The charging positive electrode 14b and the charging catalyst layer 16b constituting it are desirably low in porosity in order to efficiently exchange hydroxide ions with the LDH separator 12. Specifically, the porosity of the charging catalyst layer 16b is preferably 30 to 60%, more preferably 35 to 60%, and even more preferably 40 to 55%. For the same reason, the average pore size of the charging catalyst layer 16b is preferably 5 μm or less, more preferably 0.5 to 4 μm, and even more preferably 1 to 3 μm. The porosity and average pore diameter of the charging catalyst layer 16b can be measured by a) polishing the cross section of the LDH separator with a cross-section polisher (CP), b) acquiring two cross-sectional images of the charging catalyst layer 16b at a magnification of 10,000 times with a SEM (scanning electron microscope), c) binarizing the image using image analysis software (e.g., Image-J) based on the image data of the acquired cross-sectional images, d) determining the area of each pore for each of the two fields of view, calculating the porosity and the pore diameter of each pore, and taking the average value of these as the porosity and average pore diameter of the charging catalyst layer 16b. The pore diameter can be calculated by converting the length per pixel of the image from the actual size, assuming that each pore is a perfect circle, dividing the area of each pore obtained from the image analysis by pi, and multiplying the square root by 2, and the porosity can be calculated by dividing the number of pixels corresponding to the pores by the number of pixels in the total area and multiplying by 100.
[0032] The charging positive electrode 14b can be manufactured by preparing a paste containing a hydroxide ion conductive material, a conductive material, an organic polymer, and an air electrode catalyst, and applying the paste to the surface of the LDH separator. The paste can be prepared by adding an organic polymer (binder resin) and an organic solvent to a mixture of the hydroxide ion conductive material, the conductive material, and the air electrode catalyst, and using a known kneading machine such as a three-roll mill. Preferred examples of the organic solvent include alcohols such as butyl carbitol and terpineol, and acetate ester solvents such as butyl acetate. The paste can be applied to the LDH separator 12 by printing. This printing can be performed by various known printing methods, but is preferably performed by screen printing.
[0033] water absorption and release layer The water absorbing and discharging layer 20 is preferably disposed in the lower part of the battery case 30 so as to be in contact with the discharge positive electrode 14a and the charge positive electrode 14b that sandwich the negative electrode layer 22. The water absorbing and discharging action of the water absorbing and discharging layer 20 makes it possible to absorb the water generated by the charge reaction in the charge positive electrode 14b and to supply the water required for the discharge reaction that occurs in the discharge positive electrode 14a. In this way, the water absorbing and discharging action of the water absorbing and discharging layer 20 makes it possible to keep the charge positive electrode 14b and the discharge positive electrode 14a moist without drying them out, so that the water generated or consumed in the discharge positive electrode 14a can be circulated from the charge positive electrode 14b, and the charge and discharge reaction can be promoted.
[0034] The water absorbing and releasing layer 20 is not particularly limited as long as it has a space for absorbing and releasing moisture, but is preferably in the form of a fiber or strip. Also, the water absorbing and releasing layer 20 desirably contains a water absorbing material having water absorbing properties in order to retain moisture. Examples of the water absorbing material include water absorbing resins such as acrylamide polymers, polyvinyl alcohol polymers, and polyethylene oxide polymers, highly moisture absorbing and releasing fibers such as cellulose fibers and acrylate fibers, and any combination thereof.
[0035] In addition, in order to allow moisture diffused from the water absorption and release layer 20 toward the outside of the battery case 30 to be diffused back into the water absorption and release layer 20, it is desirable to provide a water-repellent layer 28 between the charging positive electrode 14b and the discharging positive electrode 14a and the battery case 30.
[0036] The water-repellent layer 28 means a layer that mainly repels water but does not substantially absorb water, and only allows gas to pass through to the inside and outside of the battery case 30, and may have any configuration as long as it helps the circulation of water in the water absorbing and releasing layer 20, the charge positive electrode 14b, and the discharge positive electrode 14a. For example, carbon paper or carbon cloth with a porosity of about 80% can be used.
[0037] That is, as described above, the metal-air secondary battery 10 using the LDH separator 12 has the excellent advantage of being able to prevent both short-circuiting between the positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide. In addition, the denseness of the LDH separator 12 has the advantage of being able to suppress evaporation of water contained in the electrolyte. However, since the LDH separator 12 prevents the electrolyte from penetrating into the air electrode layer 14, no electrolyte is present in the air electrode layer 14. Therefore, compared to a zinc-air secondary battery using a general separator (e.g., a porous polymer separator) that allows the electrolyte to penetrate into the air electrode layer 14, the circulation of water consumed or generated in the air electrode tends to be low, leading to a decrease in charge / discharge performance. In this regard, the water absorbing / releasing layer 20 conveniently solves such problems.
[0038] The details of the mechanism are not necessarily clear, but it is believed to be as follows. First, since the charging positive electrode 14b includes a porous current collector, it can function as a layer responsible for current collection and gas diffusion as the gas diffusion electrode 18. However, by supporting LDH on the surface of the porous current collector, it can have catalytic performance and hydroxide ion conductivity in addition to the above functions, and as a result, it is possible to secure a larger reaction area. This is because LDH, i.e., layered double hydroxide, is an ion conductive material and can also have oxygen generation catalytic ability. At this time, moisture generated by the charging reaction occurring in the charging positive electrode 14b is appropriately absorbed by the water absorption and release layer 20 that contacts the charging positive electrode 14b at the lower part. Since the discharging positive electrode 14a also includes a porous current collector like the charging positive electrode 14b, it can function as a layer responsible for current collection and gas diffusion as the gas diffusion electrode 18. Furthermore, by supporting an oxygen reduction catalyst on the surface of the porous current collector, it is possible to secure a larger reaction area. At this time, the moisture consumed by the discharge positive electrode 14a is appropriately supplied by capillary action from the water absorbing and releasing layer 20 that is in contact with the discharge positive electrode 14a at the lower part. It is believed that the advantageous combination of the functions of the discharge positive electrode 14a, the charge positive electrode 14b, and the water absorbing and releasing layer 20 in this manner has made it possible to realize excellent charge and discharge performance while maintaining the advantages of using the LDH separator 12.
[0039] LDH separator according to a preferred embodiment The LDH separator 12 according to a preferred embodiment of the present invention will be described below. Although the following description is based on a zinc-air secondary battery, the LDH separator 12 according to this embodiment can also be applied to other metal-air secondary batteries such as lithium-air secondary batteries. As described above, the LDH separator 12 according to this embodiment includes a porous substrate 12a and a hydroxide ion-conducting layered compound 12b, which is an LDH and / or an LDH-like compound, as conceptually shown in FIG. 4. In FIG. 4, the region of the hydroxide ion-conducting layered compound 12b is depicted as not being connected between the upper and lower surfaces of the LDH separator 12, but this is because it is depicted two-dimensionally as a cross section. In a three-dimensional view taking into account the depth, the region of the hydroxide ion-conducting layered compound 12b is connected between the upper and lower surfaces of the LDH separator 12, thereby ensuring the hydroxide ion conductivity of the LDH separator 12. The porous substrate 12a is made of a polymer material, and the pores of the porous substrate 12a are blocked by the hydroxide ion-conducting layered compound 12b. However, the pores of the porous substrate 12a do not need to be completely blocked, and there may be a small amount of residual pores P. By thus blocking the pores of the polymeric porous substrate 12a with the hydroxide ion-conductive layered compound 12b to highly densify it, it is possible to provide an LDH separator 12 that can more effectively suppress short circuits caused by zinc dendrites.
[0040] Furthermore, the LDH separator 12 of this embodiment not only has the desired ion conductivity required for a separator based on the hydroxide ion conductivity of the hydroxide ion conductive layered compound 12b, but also has excellent flexibility and strength. This is due to the flexibility and strength of the polymeric porous substrate 12a itself contained in the LDH separator 12. That is, the pores of the polymeric porous substrate 12a are sufficiently blocked by the hydroxide ion conductive layered compound 12b to make the LDH separator 12 dense, so that the polymeric porous substrate 12a and the hydroxide ion conductive layered compound 12b are integrated as a highly composite material, and therefore the rigidity and brittleness caused by the hydroxide ion conductive layered compound 12b, which is a ceramic material, are offset or reduced by the flexibility and strength of the polymeric porous substrate 12a.
[0041] It is desirable that the LDH separator 12 of this embodiment has very few residual pores P (pores not blocked by the hydroxide ion conductive layered compound 12b). Due to the residual pores P, the LDH separator 12 has an average porosity of, for example, 0.03% or more and less than 1.0%, preferably 0.05% or more and 0.95% or less, more preferably 0.05% or more and 0.9% or less, even more preferably 0.05 to 0.8%, and most preferably 0.05 to 0.5%. When the average porosity is within the above range, the pores of the porous substrate 12a are sufficiently blocked by the hydroxide ion conductive layered compound 12b, resulting in a very high degree of denseness, and therefore short circuits caused by zinc dendrites can be more effectively suppressed. In addition, a significantly high ion conductivity can be realized, and the LDH separator 12 can exhibit a sufficient function as a hydroxide ion conductive separator. The average porosity can be measured by a) polishing the cross section of the LDH separator with a cross-section polisher (CP), b) obtaining two cross-sectional images of the functional layer at 50,000x magnification using a FE-SEM (field emission scanning electron microscope), and c) calculating the porosity of each of the two fields of view using image inspection software (e.g., HDevelop, manufactured by MVTec Software) based on the image data of the obtained cross-sectional images, and then calculating the average value of the obtained porosities.
[0042] The LDH separator 12 is a separator containing a hydroxide ion conductive layered compound 12b, and when incorporated in a zinc secondary battery, it separates the positive electrode plate and the negative electrode plate in a manner that allows hydroxide ion conductivity. That is, the LDH separator 12 functions as a hydroxide ion conductive separator. Therefore, the LDH separator 12 has gas impermeability and / or water impermeability. Therefore, it is preferable that the LDH separator 12 is densified to have gas impermeability and / or water impermeability. In this specification, "having gas impermeability" means that, as described in Patent Documents 2 and 3, even if helium gas is brought into contact with one side of the object to be measured in water at a differential pressure of 0.5 atm, no bubbles due to helium gas are generated from the other side. In addition, in this specification, "having water impermeability" means that water that has come into contact with one side of the object to be measured does not penetrate to the other side, as described in Patent Documents 2 and 3. That is, the LDH separator 12 being gas-impermeable and / or water-impermeable means that the LDH separator 12 is dense enough to prevent gas or water from passing through, and is not a porous film or other porous material having water or gas permeability. In this way, the LDH separator 12 selectively passes only hydroxide ions due to its hydroxide ion conductivity, and can function as a battery separator. Therefore, the LDH separator 12 is extremely effective in preventing short-circuiting between the positive and negative electrodes by physically preventing the penetration of the separator by zinc dendrites generated during charging. Since the LDH separator 12 has hydroxide ion conductivity, it is possible to efficiently move hydroxide ions required between the positive and negative electrode plates, thereby realizing charge / discharge reactions in the positive and negative electrode plates.
[0043] The LDH separator 12 preferably has a He permeability per unit area of 3.0 cm / min·atm or less, more preferably 2.0 cm / min·atm or less, and even more preferably 1.0 cm / min·atm or less. A separator with a He permeability of 3.0 cm / min·atm or less can very effectively suppress the permeation of Zn (typically the permeation of zinc ions or zincate ions) in an electrolyte. In this way, the separator of this embodiment is considered in principle to be able to effectively suppress the growth of zinc dendrites when used in a zinc secondary battery by significantly suppressing Zn permeation. The He permeability is measured through a process of supplying He gas to one side of the separator to allow the He gas to permeate the separator, and a process of calculating the He permeability to evaluate the denseness of the hydroxide ion conductive separator. The He permeability is calculated by the formula F / (P×S) using the amount of He gas permeated per unit time F, the pressure difference P applied to the separator when He gas permeates, and the membrane area S through which He gas permeates. By evaluating gas permeability using He gas in this way, it is possible to evaluate the presence or absence of denseness at an extremely high level, and as a result, it is possible to effectively evaluate a high level of denseness, such as not allowing substances other than hydroxide ions (especially Zn, which causes zinc dendrite growth) to permeate as much as possible (permeating only a very small amount). This is because He gas has the smallest structural unit among the wide variety of atoms or molecules that can constitute gas, and has extremely low reactivity. In other words, He does not form molecules, and He gas is composed of He atoms alone. In this regard, hydrogen gas is composed of H2 molecules, so that He atoms alone are smaller as a gas structural unit. In the first place, H2 gas is dangerous because it is a flammable gas. And by adopting the index of He gas permeability defined by the above formula, it is possible to easily and objectively evaluate denseness regardless of various sample sizes and differences in measurement conditions. In this way, it is possible to simply, safely, and effectively evaluate whether the separator has a sufficiently high density suitable for a zinc secondary battery separator. The He permeability can be preferably measured according to the procedure shown in Evaluation 4 of the Examples described later.
[0044] In the LDH separator 12, the pores of the porous substrate 12a are filled with hydroxide ion conductive layered compounds 12b, which are LDHs and / or LDH-like compounds. As is generally known, LDHs are composed of multiple hydroxide basic layers and intermediate layers interposed between these multiple hydroxide basic layers. The hydroxide basic layers are mainly composed of metal elements (typically metal ions) and OH groups. The intermediate layers of the LDHs are composed of anions and HO. The anions are monovalent or higher anions, preferably monovalent or divalent ions. Preferably, the anions in the LDHs are OH groups. - and / or CO3 2- In addition, LDH has excellent ionic conductivity due to its inherent properties.
[0045] In general, LDH is 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an anion with a valence of n, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more. In the above basic formula, M 2+ can be any divalent cation, but preferred examples include Mg 2+ , Ca 2+ and Zn 2+ More preferably, Mg 2+ It is. 3+ can be any trivalent cation, but preferred examples include Al 3+ or Cr 3+ More preferably, Al 3+ A n- can be any anion, but preferred examples include OH - and CO3 2- Therefore, in the above basic composition formula, M 2+ Mg 2+ Including M 3+ Al 3+ Including An- OH - and / or CO3 2- It is preferable that the formula contains the formula. n is an integer of 1 or more, preferably 1 or 2. x is 0.1 to 0.4, preferably 0.2 to 0.35. m is an arbitrary number representing the number of moles of water, and is a real number of 0 or more, typically exceeding 0 or 1 or more. However, the above basic composition formula is merely a formula of a "basic composition" typically exemplified for LDH, and the constituent ions can be appropriately replaced. For example, in the above basic composition formula, M 3+ may be replaced in part or in whole with a cation having a valence of 4 or more. In that case, the anion A in the above general formula may be replaced with n- The coefficient x / n may be changed as appropriate.
[0046] For example, the hydroxide base layer of the LDH may contain Ni, Al, Ti, and OH groups. As described above, the intermediate layer is composed of anions and H2O. The alternately laminated structure of the hydroxide base layer and intermediate layer itself is basically the same as the alternately laminated structure of the commonly known LDH, but the LDH of this embodiment can exhibit excellent alkali resistance by forming the hydroxide base layer of the LDH with a specific element or ion including Ni, Al, Ti, and OH groups. Although the reason is not necessarily clear, it is thought that in the LDH of this embodiment, Al, which was previously thought to be easily dissolved in an alkaline solution, is difficult to dissolve in an alkaline solution due to some interaction with Ni and Ti. Nevertheless, the LDH of this embodiment can also exhibit high ionic conductivity suitable for use as a separator for an alkaline secondary battery. Ni in the LDH can take the form of nickel ions. Nickel ions in the LDH are typically Ni 2+ However, Ni 3+ The valence of the Al in the LDH can be in the form of an aluminum ion. The aluminum ion in the LDH is typically Al 3+ However, other valences are possible, so there is no particular limitation. Ti in LDH can take the form of a titanium ion. Titanium ions in LDH are typically Ti 4+Although it is considered to be, other valences such as Ti 3+ etc. are also possible and are not particularly limited. As long as the hydroxide basic layer contains Ni, Al, Ti and OH groups, it may contain other elements or ions. However, the hydroxide basic layer preferably contains Ni, Al, Ti and OH groups as main components. That is, the hydroxide basic layer preferably consists mainly of Ni, Al, Ti and OH groups. Therefore, the hydroxide basic layer is typically composed of Ni, Al, Ti, OH groups and optionally inevitable impurities. Inevitable impurities are any elements that can be inevitably mixed in during the manufacturing process, for example, elements that can be mixed into the LDH from raw materials or substrates. As described above, since the valences of Ni, Al and Ti are not necessarily determined, it is impractical or impossible to precisely specify the LDH by a general formula. Assuming that the hydroxide basic layer is mainly composed of Ni 2+ , Al 3+ , Ti 4+ and OH groups, the corresponding LDH has the general formula: Ni 2+ 1-x-y Al 3+ x Ti 4+ y (OH)2A n- (x+2y) / n ·mH2O (where A n- is an n-valent anion, n is an integer of 1 or more, preferably 1 or 2, 0 < x < 1, preferably 0.01 ≦ x ≦ 0.5, 0 < y < 1, preferably 0.01 ≦ y ≦ 0.5, 0 < x + y < 1, m is 0 or more, typically a real number exceeding 0 or 1 or more) and can be represented by the basic composition. However, the above general formula should be understood as the "basic composition" at most, and elements such as Ni 2+ , Al 3+ , Ti 4+ etc. should be understood as replaceable with other elements or ions (including elements or ions of other valences of the same element or elements or ions that can be inevitably mixed in during the manufacturing process) to the extent that they do not impair the basic properties of the LDH.
[0047] The LDH-like compound is a hydroxide and / or oxide having a layered crystal structure similar to LDH, although it may not be called LDH. A preferred LDH-like compound will be described later. By using an LDH-like compound, which is a hydroxide and / or oxide having a layered crystal structure having a specific composition as described later, as a hydroxide ion conductive material instead of the conventional LDH, it is possible to provide a hydroxide ion conductive separator that is excellent in alkali resistance and can more effectively suppress short circuits caused by zinc dendrites.
[0048] As described above, the LDH separator 12 includes the hydroxide ion-conducting layered compound 12b and the porous substrate 12a (typically consisting of the porous substrate 12a and the hydroxide ion-conducting layered compound 12b), and the hydroxide ion-conducting layered compound fills the pores of the porous substrate so that the LDH separator 12 exhibits hydroxide ion conductivity and gas impermeability (and therefore functions as an LDH separator exhibiting hydroxide ion conductivity). It is particularly preferred that the hydroxide ion-conducting layered compound 12b is incorporated throughout the entire thickness of the polymeric porous substrate 12a. The thickness of the LDH separator is preferably 3 to 80 μm, more preferably 3 to 60 μm, and even more preferably 3 to 40 μm.
[0049] The porous substrate 12a is made of a polymer material. The polymer porous substrate 12a has the following advantages: 1) flexibility (hence it is difficult to break even if it is thinned); 2) the porosity can be easily increased; 3) the conductivity can be easily increased (because the thickness can be reduced while increasing the porosity); and 4) it is easy to manufacture and handle. In addition, by utilizing the advantage derived from the flexibility of the above 1), it has the advantage of 5) being easy to fold or seal and bond the LDH separator including the porous substrate made of a polymer material. Preferable examples of the polymer material include polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), cellulose, nylon, polyethylene, and any combination thereof. More preferably, from the viewpoint of a thermoplastic resin suitable for hot pressing, polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), nylon, polyethylene, and any combination thereof. All of the above-mentioned various preferable materials have alkali resistance as resistance to the electrolyte of the battery. Particularly preferred polymeric materials are polyolefins such as polypropylene and polyethylene, which are excellent in hot water resistance, acid resistance and alkali resistance, and are low cost, and are most preferably polypropylene or polyethylene. When the porous substrate is made of a polymeric material, it is particularly preferred that the hydroxide ion-conducting layered compound is incorporated throughout the entire thickness of the porous substrate (e.g., most or almost all of the pores inside the porous substrate are filled with the hydroxide ion-conducting layered compound). As such a polymeric porous substrate, a commercially available polymeric microporous membrane can be preferably used.
[0050] The LDH separator of this embodiment can be manufactured by (i) preparing a composite material containing a hydroxide ion conductive layered compound using a polymeric porous substrate according to a known method (see, for example, Patent Documents 1 to 3), and (ii) pressing the composite material containing the hydroxide ion conductive layered compound. The pressing method may be, for example, roll pressing, uniaxial pressing, CIP (cold isostatic pressing), etc., and is not particularly limited, but roll pressing is preferred. This pressing is preferably performed while heating, since it softens the polymeric porous substrate, thereby allowing the pores of the porous substrate to be sufficiently blocked with the hydroxide ion conductive layered compound. For example, in the case of polypropylene or polyethylene, it is preferable to heat the substrate to a temperature of 60 to 200°C, which is sufficient for sufficient softening. By performing pressing such as roll pressing in such a temperature range, the average porosity derived from the residual pores of the LDH separator can be significantly reduced. As a result, the LDH separator can be extremely highly densified, and therefore short circuits caused by zinc dendrites can be more effectively suppressed. When performing roll pressing, the shape of the residual pores can be controlled by appropriately adjusting the roll gap and roll temperature, thereby making it possible to obtain an LDH separator with the desired density or average porosity.
[0051] The method for producing the hydroxide ion conductive layered compound-containing composite material (i.e., crude LDH separator) before pressing is not particularly limited, and it can be produced by appropriately modifying the conditions of the already known methods for producing LDH-containing functional layers and composite materials (i.e., LDH separators) (see, for example, Patent Documents 1 to 3). For example, (1) a porous substrate is prepared, (2) a titanium oxide sol or a mixed sol of alumina and titania is applied to the porous substrate and heat-treated to form a titanium oxide layer or an alumina-titania layer, and (3) nickel ions (Ni 2+(4) immersing the porous substrate in a raw aqueous solution containing urea and urea, and (5) hydrothermally treating the porous substrate in the raw aqueous solution to form a functional layer containing a hydroxide ion-conducting layered compound on and / or in the porous substrate, thereby producing a hydroxide ion-conducting layered compound-containing functional layer and a composite material (i.e., LDH separator). In particular, forming a titanium oxide layer or an alumina-titania layer on the porous substrate in the above step (2) not only provides the raw material for the hydroxide ion-conducting layered compound, but also functions as a starting point for the crystal growth of the hydroxide ion-conducting layered compound, thereby forming a highly densified hydroxide ion-conducting layered compound-containing functional layer uniformly without unevenness in the porous substrate. In addition, the presence of urea in the above step (3) increases the pH value by generating ammonia in the solution by utilizing the hydrolysis of urea, and the coexisting metal ions form hydroxides to obtain a hydroxide ion-conducting layered compound. In addition, since carbon dioxide is generated during the hydrolysis, a hydroxide ion-conducting layered compound in which the anion is a carbonate ion can be obtained.
[0052] In particular, when preparing a composite material (i.e., an LDH separator) in which the porous substrate is made of a polymer material and the functional layer is incorporated throughout the entire thickness of the porous substrate, it is preferable to apply the mixed sol of alumina and titania to the substrate in (2) above in such a manner that the mixed sol penetrates the entire or most of the substrate. In this way, most or almost all of the pores in the porous substrate can be filled with the hydroxide ion conductive layered compound. Examples of preferred application methods include dip coating and filtration coating, and dip coating is particularly preferred. The amount of the mixed sol attached can be adjusted by adjusting the number of applications of dip coating, etc. The substrate to which the mixed sol has been applied by dip coating, etc. may be dried and then subjected to the above steps (3) and (4).
[0053] LDH-like compounds According to a preferred embodiment of the present invention, the LDH separator may contain an LDH-like compound. The definition of the LDH-like compound is as described above. Preferred LDH-like compounds are: (a) a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al, or (b) a hydroxide and / or oxide having a layered crystal structure containing (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M which is at least one selected from the group consisting of In, Bi, Ca, Sr, and Ba; or (c) A hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, in which the LDH-like compound is present in the form of a mixture with In(OH)3.
[0054] According to a preferred embodiment (a) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, optionally Y, and optionally Al. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. For example, the LDH-like compound may further contain Zn and / or K. This can further improve the ionic conductivity of the LDH separator.
[0055] The LDH-like compound can be identified by X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of the LDH separator, a peak derived from the LDH-like compound is typically detected in the range of 5°≦2θ≦10°, more typically in the range of 7°≦2θ≦10°. As described above, LDH is a substance having an alternating laminate structure in which exchangeable anions and H2O exist as intermediate layers between stacked hydroxide basic layers. In this regard, when LDH is measured by X-ray diffraction, a peak due to the crystal structure of LDH (i.e., the (003) peak of LDH) is essentially detected at a position of 2θ=11 to 12°. In contrast, when an LDH-like compound is measured by X-ray diffraction, a peak is typically detected in the above-mentioned range shifted to the lower angle side from the above-mentioned peak position of LDH. In addition, the interlayer distance of the layered crystal structure can be determined by the Bragg formula using 2θ corresponding to the peak derived from the LDH-like compound in X-ray diffraction. The interlayer distance of the layered crystal structure constituting the LDH-like compound thus determined is typically 0.883 to 1.8 nm, and more typically 0.883 to 1.3 nm.
[0056] In the LDH separator according to the above aspect (a), the atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. The atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. The atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. The atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within the above ranges, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Regarding LDH separators, conventionally known LDHs have the general formula: M 2+ 1-x M3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0057] According to another preferred embodiment (b) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure, comprising (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Ti, Y, the additional element M, optionally Al, and optionally Mg. The additional element M is In, Bi, Ca, Sr, Ba, or a combination thereof. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferred that the LDH-like compound does not contain Ni.
[0058] In the LDH separator according to the above aspect (b), the atomic ratio of Ti / (Mg+Al+Ti+Y+M) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.50 to 0.85, more preferably 0.56 to 0.81. The atomic ratio of Y / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.20, more preferably 0.07 to 0.15. The atomic ratio of M / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.35, more preferably 0.03 to 0.32. The atomic ratio of Mg / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.10, more preferably 0 to 0.02. The atomic ratio of Al / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.04. Within the above range, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Incidentally, LDHs conventionally known as LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0059] According to yet another preferred embodiment (c) of the present invention, the LDH-like compound is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, and the LDH-like compound may be present in the form of a mixture with In(OH)3. The LDH-like compound of this embodiment is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, Y, optionally Al, and optionally In. The In that may be contained in the LDH-like compound may not only be that which is intentionally added to the LDH-like compound, but may also be that which is inevitably mixed into the LDH-like compound due to the formation of In(OH)3 or the like. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. Incidentally, LDHs conventionally known for LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. Therefore, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH.
[0060] The mixture according to the above embodiment (c) contains not only an LDH-like compound but also In(OH)3 (typically composed of an LDH-like compound and In(OH)3). The inclusion of In(OH)3 can effectively improve the alkali resistance and dendrite resistance of the LDH separator. The content ratio of In(OH)3 in the mixture is preferably an amount that can improve the alkali resistance and dendrite resistance without substantially impairing the hydroxide ion conductivity of the LDH separator, and is not particularly limited. In(OH)3 may have a cubic crystal structure, or may have a structure in which In(OH)3 crystals are surrounded by the LDH-like compound. In(OH)3 can be identified by X-ray diffraction. EXAMPLES
[0061] The present invention will now be further illustrated by the following examples.
[0062] Example A1 The LDH separator was prepared by the following procedure and evaluated.
[0063] (1) Preparation of polymeric porous substrate A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 20 μm was prepared as a polymeric porous substrate, and cut to a size of 2.0 cm×2.0 cm.
[0064] (2) Alumina-titania sol coating on polymeric porous substrate A mixed sol was prepared by mixing an amorphous alumina solution (Al-ML15, Taki Chemical Co., Ltd.) and a titanium oxide sol solution (M6, Taki Chemical Co., Ltd.) so that the Ti / Al (molar ratio) was 2. The mixed sol was applied by dip coating to the substrate prepared in (1) above. The dip coating was performed by immersing the substrate in 100 ml of the mixed sol, then pulling it up vertically, and drying it in a dryer at 90°C for 5 minutes.
[0065] (3) Preparation of raw solution Nickel nitrate hexahydrate (Ni(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma-Aldrich) were prepared as raw materials. Nickel nitrate hexahydrate was weighed out and placed in a beaker so that the concentration was 0.015 mol / L, and ion-exchanged water was added to make the total volume 75 ml. The resulting solution was stirred, and then urea / NO3 - Urea weighed out in a molar ratio of 16 was added, and the mixture was further stirred to obtain a raw material aqueous solution.
[0066] (4) Film formation by hydrothermal treatment The raw material aqueous solution and the dip-coated substrate were both sealed in a Teflon (registered trademark) sealed container (autoclave container, capacity 100 ml, outer stainless steel jacket). At this time, the substrate was fixed by floating it from the bottom of the Teflon (registered trademark) sealed container, and placed horizontally so that the solution was in contact with both sides of the substrate. Thereafter, LDH was formed on the surface and inside of the substrate by performing hydrothermal treatment at a hydrothermal temperature of 120°C for 24 hours. After a predetermined time had passed, the substrate was removed from the sealed container, washed with ion-exchanged water, and dried at 70°C for 10 hours to form LDH in the pores of the porous substrate. In this way, a composite material containing LDH was obtained.
[0067] (5) Densification by roll pressing The composite material containing the above LDH was sandwiched between a pair of PET films (Lumirror (registered trademark), manufactured by Toray Industries, Inc., thickness 40 μm) and roll pressed at a roll rotation speed of 3 mm / s, a roll temperature of 120° C., and a roll gap of 60 μm to obtain an LDH separator.
[0068] (6) Evaluation results The obtained LDH separator was evaluated as follows.
[0069] Rating 1 : Identification of LDH separator The crystalline phase of the LDH separator was measured using an X-ray diffractometer (Rigaku Corporation, RINT TTR III) under the following measurement conditions: voltage: 50 kV, current value: 300 mA, measurement range: 10 to 70° to obtain an XRD profile. The obtained XRD profile was identified using the diffraction peak of LDH (hydrotalcite compound) described in JCPDS card No. 35-0964. The LDH separator of this example was identified as LDH (hydrotalcite compound).
[0070] Rating 2 : Thickness measurement The thickness of the LDH separator was measured using a micrometer. The thickness was measured at three points, and the average value was adopted as the thickness of the LDH separator. As a result, the thickness of the LDH separator in this example was 13 μm.
[0071] Rating 3 : Average porosity measurement The cross-section of the LDH separator was polished using a cross-section polisher (CP), and two cross-sectional images of the LDH separator were obtained at a magnification of 50,000 times using a FE-SEM (ULTRA55, manufactured by Carl Zeiss). Based on this image data, the porosity of each of the two fields was calculated using image inspection software (HDevelop, manufactured by MVTec Software), and the average value was taken as the average porosity of the LDH separator. As a result, the average porosity of the LDH separator in this example was 0.8%.
[0072] Rating 4 :He transmission measurement In order to evaluate the denseness of the LDH separator from the viewpoint of He permeability, a He permeability test was carried out as follows. First, a He permeability measurement system 310 shown in Figures 5A and 5B was constructed. The He permeability measurement system 310 was configured so that He gas from a gas cylinder filled with He gas was supplied to a sample holder 316 via a pressure gauge 312 and a flow meter 314 (digital flow meter), and the He gas was permeated from one side of an LDH separator 318 held by this sample holder 316 to the other side and discharged.
[0073] The sample holder 316 has a structure including a gas supply port 316a, a sealed space 316b, and a gas exhaust port 316c, and was assembled as follows. First, an adhesive 322 was applied along the outer periphery of the LDH separator 318, and the LDH separator 318 was attached to a jig 324 (made of ABS resin) having an opening in the center. Butyl rubber packings were arranged as sealing members 326a, 326b at the upper and lower ends of the jig 324, and the sealing members 326a, 326b were sandwiched from the outside by support members 328a, 328b (made of PTFE) having openings made of flanges. In this way, the LDH separator 318, the jig 324, the sealing member 326a, and the support member 328a defined a sealed space 316b. The support members 328a, 328b were tightly fastened together by a fastening means 330 using screws so that He gas would not leak from any part other than the gas exhaust port 316c. A gas supply pipe 334 was connected via a joint 332 to a gas supply port 316 a of the sample holder 316 thus assembled.
[0074] Next, He gas was supplied to the He permeability measurement system 310 via the gas supply pipe 334, and was allowed to permeate through the LDH separator 318 held in the sample holder 316. At this time, the gas supply pressure and flow rate were monitored by the pressure gauge 312 and the flow meter 314. After the He gas permeation was carried out for 1 to 30 minutes, the He permeability was calculated. The He permeability was calculated based on the amount of He gas permeated per unit time F (cm 3 / min), the pressure difference P (atm) applied to the LDH separator when He gas permeates, and the membrane area S (cm 2 ) was used to calculate the amount of He gas permeation F (cm 3 / min) was read directly from flowmeter 314. The differential pressure P was the gauge pressure read from pressure gauge 312. He gas was supplied so that the differential pressure P was in the range of 0.05 to 0.90 atm. As a result, the He permeability per unit area of the LDH separator was 0.0 cm / min atm.
[0075] Rating 5 : Observation of the microstructure of the separator surface When the surface of the LDH separator was observed by SEM, it was found that numerous LDH plate-like particles were bonded perpendicularly or obliquely to the main surface of the LDH separator, as shown in FIG.
[0076] Example B1 Using the LDH separator produced in Example A1, a zinc-air secondary battery equipped with an air electrode / separator assembly was produced in the following manner, and the battery was evaluated.
[0077] (1) Preparation of cathode catalyst for charging (1 a ) Iron oxide sol coating on conductive porous substrate 10 ml of iron oxide sol (Fe-C10, iron oxide concentration 10% by weight, manufactured by Taki Chemical Industry Co., Ltd.) diluted with ion-exchanged water to a concentration of 5% by weight was placed in a beaker, and carbon paper (TGP-H-060, manufactured by Toray, thickness 200 μm) was immersed in the sol. A vacuum was applied to the beaker, allowing the iron oxide sol to fully penetrate into the carbon paper. The carbon paper was pulled out of the beaker with tweezers and dried at 80°C for 30 minutes to obtain carbon paper with iron oxide particles attached as a substrate.
[0078] (1b) Preparation of raw solution Nickel nitrate hexahydrate (Ni(NO3)2 6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Mitsui Chemicals, Inc.) were prepared as raw materials. Nickel nitrate hexahydrate was weighed out and placed in a beaker so that the concentration was 0.03 mol / L, and ion-exchanged water was added to make the total volume 75 ml. The resulting solution was stirred, and then urea was added to the solution so that the concentration was 0.96 mol / L, and further stirring was performed to obtain a raw material aqueous solution.
[0079] (1c) Film formation by hydrothermal treatment The raw material aqueous solution prepared in (1b) and the raw material aqueous solution prepared in (1) were placed in a Teflon (registered trademark) airtight container (autoclave container, capacity 100 ml, outer jacket made of stainless steel). a) was enclosed. At this time, the substrate was fixed by floating it from the bottom of a Teflon (registered trademark) sealed container, and placed horizontally so that both sides of the substrate were in contact with the solution. Then, LDH was formed on the surface of the fibers inside the substrate by performing hydrothermal treatment at a hydrothermal temperature of 120°C for 20 hours. After a predetermined time had passed, the substrate was taken out of the sealed container, washed with ion-exchanged water, and dried at 80°C for 30 minutes to obtain a catalyst layer as an air cathode layer. When the microstructure of the obtained catalyst layer was observed by SEM, the images shown in Figures 7A to 7C were obtained. Figure 7B is an enlarged image of the carbon fiber surface constituting the carbon paper shown in Figure 7A, and Figure 7C is an enlarged image of a cross section near the surface of the carbon fiber shown in Figure 7A. From these figures, it was observed that countless LDH plate-like particles were bonded vertically or obliquely to the surface of the carbon fibers constituting the carbon paper, and the LDH plate-like particles were connected to each other.
[0080] The porosity of the resulting rechargeable positive electrode was measured by mercury intrusion porosimetry and was found to be 76%.
[0081] (2) Bonding of the charging positive electrode and the LDH separator Carbon powder (Denka Black, manufactured by Denka Co., Ltd.) was added at 5% by weight to ethanol (Kanto Chemical Co., Ltd., purity 99.5%) and dispersed by ultrasonic waves to prepare a carbon slurry. The obtained slurry was applied by spin coating onto the LDH separator obtained in Example A1, and then the charging positive electrode was placed on it. A weight was placed on the charging positive electrode and it was dried at 80°C in air for 2 hours. In this way, a charging positive electrode (thickness 200 μm) was formed on the LDH separator. At this time, an interface layer (thickness 0.2 μm) containing LDH plate-like particles (derived from the LDH separator) and carbon (derived from the carbon slurry) was simultaneously formed between the LDH separator and the charging positive electrode. That is, a charging positive electrode / separator assembly was obtained.
[0082] (3) Bonding of the discharge positive electrode and the LDH separator 25 parts by weight of carbon powder (Tokai Carbon Co., Ltd., Toka Black #3855), 23 parts by weight of LDH powder (Ni-Fe-LDH powder prepared by coprecipitation method), 8 parts by weight of platinum-supported carbon (Toyo Corporation, EC-20-PTC), 5 parts by weight of butyral resin, and 39 parts by weight of butyl carbitol were added and kneaded with a three-roll and a rotation-revolution mixer (Thinky Corporation, ARE-310) to form a paste. This paste was applied by screen printing to the surface of the LDH separator prepared in Example A1 to prepare a discharge positive electrode catalyst layer. Before the prepared paste was dried, a gas diffusion electrode (SIGRACET29BC) was placed on it, and it was dried for 30 minutes at 80°C in the air under a weight to obtain a discharge positive electrode / separator assembly.
[0083] (4) Preparation of water absorbing and releasing layer Polyvinyl alcohol (160-11485, Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in ion-exchanged water to a 10% by weight aqueous solution, and impregnated into a nonwoven fabric (FT-7040P, Japan Vilene Co., Ltd.). The impregnated nonwoven fabric was sandwiched between a pair of plates to a thickness of 1.5 mm and dried. The nonwoven fabric was removed from the plates and immersed again in ion-exchanged water for 1 hour, and then cut into a size (width 5 mm) that fit the outer circumference of the electrode while still absorbing water, to prepare a water absorbing and releasing layer.
[0084] (5) Preparation of zinc oxide anode 100 parts by weight of ZnO powder (manufactured by Seido Chemical Industry Co., Ltd., JIS standard type 1 grade, average particle diameter D50: 0.2 μm) was added with 5 parts by weight of metal Zn powder (manufactured by Mitsui Mining & Smelting Co., Ltd., doped with Bi and In, Bi: 1000 ppm by weight, In: 1000 ppm by weight, average particle diameter D50: 100 μm), and 1.26 parts by weight of polytetrafluoroethylene (PTFE) dispersion solution (manufactured by Daikin Industries, Ltd., solid content 60%) was added in solid content equivalent, and kneaded with propylene glycol. The kneaded product was rolled with a roll press to obtain a negative electrode active material sheet of 0.4 mm. The negative electrode active material sheet was then pressed onto a tin-plated copper expand metal, and dried at 80 ° C. for 14 hours in a vacuum dryer. The dried negative electrode sheet was cut so that the part coated with the active material was 2 cm square, and Cu foil was welded to the current collector part to obtain a zinc oxide negative electrode.
[0085] (6) Catalyst layer thickness measurement Before forming the catalyst layer, the thickness of the LDH separator and the gas diffusion electrode were each measured at three locations using a micrometer, and the average value was used as the thickness. After fabricating the air electrode / separator assembly, the thickness of the air electrode / separator assembly was measured at three locations, and the average value minus the thickness of the LDH separator and the gas diffusion electrode was used as the thickness of the catalyst layer. As a result, the thickness of the catalyst layer in this example was 15 μm.
[0086] (7) Water absorption test of water absorption and release layer As in (4) above, the dried body of the water absorbing and releasing layer was cut into 1.5 cm squares, weighed, and then immersed in ion-exchanged water for 1 hour. After 1 hour, the water absorbing and releasing layer was taken out, placed on Kimwipe for 15 seconds to drain water, and then weighed. The amount of water absorption was calculated using the following formula, and was found to be 20 g / g. (Weight of water absorption / discharge layer after water absorption [g] - Weight of water absorption / discharge layer before water absorption [g]) / (Weight of water absorption / discharge layer before water absorption [g])
[0087] (8) Assembly and evaluation of evaluation cells As shown in FIG. 8, the discharge positive electrode 14a / separator 12 assembly and the charge positive electrode 14b / separator 12 assembly were arranged so that the LDH separators 12 faced each other, and a nonwoven fabric 24 impregnated with an electrolyte and a metal zinc plate (negative electrode 26) were sandwiched between them. At this time, a 5.4 M KOH aqueous solution saturated with zinc oxide was used as the electrolyte. The four peripheral edges of the obtained laminate were heat-pressed, and a water absorbing and releasing layer 20 was sandwiched in one lower edge of the laminate. A water-repellent layer 28 and a substrate with a gas flow path (corresponding to a battery case 30) were laminated on both sides (the surface of the discharge positive electrode and the surface of the charge positive electrode) of the obtained assembly, and the assembly was sandwiched with a pressing tool in a state where a sealing member was tightly bitten on the outer periphery, and was firmly fixed with a screw to obtain an evaluation cell having a configuration as shown in FIG. 9.
[0088] The charge / discharge characteristics of the evaluation cell were measured using an electrochemical measurement device (HZ-Pro S12, manufactured by Hokuto Denko Corporation) under the following conditions: Air electrode gas: Water vapor saturated (25℃) oxygen (flow rate 200cc / min) ·Charge / discharge current density: 2m / cm 2 ·Charge / discharge time: 60 minutes charge / 60 minutes discharge Number of cycles: 200 cycles The measurements were made. The results are shown in Figure 10. From Figure 10, it was found that the evaluation cell (zinc-air secondary battery) made in this example had a structure in which no electrolyte was present in the air cathode layer (which would naturally tend to increase resistance), but the increase in charge / discharge overvoltage was suppressed even after cycles.
[0089] Example B2 (comparison) An evaluation cell was prepared in the same manner as in Example B1, except that no water absorbing / releasing layer was provided in the evaluation cell, and the evaluation was carried out. The results are shown in Figure 10. From Figure 10, it was found that the evaluation cell prepared in this example did not include a water absorbing / releasing layer, and therefore the increase in charge / discharge overvoltage was large when cycled.
Claims
1. a hydroxide ion conductive separator having an internal space capable of accommodating a metal negative electrode, or a metal negative electrode and an electrolyte-containing nonwoven fabric; a pair of catalyst layers covering both sides of the hydroxide ion conductive separator, the catalyst layers including an air electrode catalyst, a hydroxide ion conductive material, and an electrically conductive material; a pair of gas diffusion electrodes disposed on opposite sides of the pair of catalyst layers from the hydroxide ion conducting separator; a water absorbing / releasing layer having water absorbing and releasing properties and provided so as to be in contact with both of the pair of catalyst layers; A cathode / separator assembly comprising: one of the pair of catalyst layers is a discharge catalyst layer, and the other of the pair of catalyst layers is a charge catalyst layer; the hydroxide ion conductive separator, the catalyst layer, and the gas diffusion electrode are arranged vertically, and the water absorbing / releasing layer is arranged horizontally below the catalyst layer so as to be in contact with a lower end of the catalyst layer.
2. The air electrode / separator assembly according to claim 1 , wherein the water absorbing / releasing layer comprises a water-absorbent resin.
3. The air electrode / separator assembly according to claim 2 , wherein the water absorbing / releasing layer further comprises silica gel.
4. 4. The air electrode / separator assembly according to claim 2, wherein the water-absorbing resin is at least one selected from the group consisting of a polyacrylamide-based resin, a potassium polyacrylate, a polyvinyl alcohol-based resin, and a cellulose-based resin.
5. 5. The air electrode / separator assembly according to claim 2, wherein the catalyst layer contains 0.01 to 10% by volume of the water-absorbing resin in terms of solid content, relative to 100% by volume of the solid content of the catalyst layer.
6. 6. The air electrode / separator assembly according to claim 1, wherein the hydroxide ion conductive material contained in the catalyst layer is a layered double hydroxide (LDH).
7. 7. The air electrode / separator assembly according to claim 1, wherein the catalyst layer contains 20 to 50% by volume of the hydroxide ion conductive material relative to 100% by volume of a solid content of the catalyst layer.
8. 8. The cathode / separator assembly of claim 1, wherein the hydroxide ion conducting separator is a layered double hydroxide (LDH) separator.
9. The cathode / separator assembly of claim 8 , wherein the LDH separator is composited with a porous substrate.
10. 10. The air electrode / separator assembly according to claim 1, wherein the hydroxide ion conductive separator having the internal space comprises a pair of hydroxide ion conductive separators facing each other or a folded hydroxide ion conductive separator, and the pair of hydroxide ion conductive separators or the folded hydroxide ion conductive separator may have edges other than their upper ends (excluding the folded edges) sealed by bonding.
11. 11. A metal-air secondary battery comprising the air electrode / separator assembly according to claim 1, a metal negative electrode accommodated in the internal space, and an electrolytic solution, wherein the water absorbing and releasing layer is positioned below the catalyst layer.
12. The metal-air secondary battery according to claim 11 , further comprising an electrolytic solution-containing nonwoven fabric in the internal space.
Citation Information
Patent Citations
Air cell
JP2007157445A
Air battery
JP2016081572A
Magnesium air battery
JP2020166990A
Zinc-air secondary battery
WO2013073292A1
Air electrode for metal-air battery
WO2015146671A1